CAIÇARA CULTURE: THE FEAST AND THE “CIRANDA” DANCES AMONG THE “CIRANDEIROS” / FISHERMEN FROM TARITUBA / PARATI / RJ. (Fiep Bulletin - online, 2013)
The aim (objective) of this study is to show how the party of Santa Cruz is revealed while a ritual and a celebration in the “caiçara” community in Tarituba. It deals about a descriptive exploratory study, with a qualitative approach, of ethnographical interpretative nature. Interviews were made and the speeches were analyses according to Eni Orlandi (2001). The origin of its people consists of the miscegenation of white, Indian and black ethnical stock and can be understood through the occupation of the Brazilian seaboard and the cycles lived by the southeastern region (ADAMS, 2000). To feel life seems that it is to represent it by the images of reception and hospitality. The people of Tarituba sing and dance their usages (customs) to celebrate work (labor) and leisure. According to DUVIGNAUD (1983), the collective parties insinuate themselves into the gaps of civilizations when they are shocked by the changes that alter (modify) the culture established. In Tarituba, at the moments of balls and dances of the dances in circle, the amusement and the transformations make evident feelings, histories and dreams of simple people who strengthen provided that they are together, sharing these moments. In some contemporary societies, which still keep a simple way of life and of local tradition, the presence of entertainment, parties, in the life of these communities, makes to arise a creative blank causing (provoking) balance as well as unbalance in the relations of labor and leisure. It is in this social dimension, in which the dances are presented, that we notice the importance of these activities in the genesis of human development regarding the demands of this same society (society itself).